Development Of A Malaysian Servant Leadership Instrument - Asmawati Mahidi; Muhammad Faizal A Ghani; Abd. Muhith; Ahmad Khuza’i Faruq (JIEMAN: Journal of Islamic Educational Management, 2023)
The development and validation of a tool to evaluate the servant leadership component of elementary school leaders in the local context is the aim of this study. This is due to the fact that most of the instruments now in use are from the west and are therefore less suitable for usage in Malaysian schools. Three servant leadership specialists tested the validity of the measure. The study's quantitative design is then tested for reliability using SPSS 26.0. Additionally, the researcher tested the instrument's reliability index using Cronbach Alpha. Then, 25 instructors who teach in the Miri area and were chosen at random to complete this instrument, which comprises of 40 items, were given copies of it via Google Form. This tool was created to assess six (6) aspects of servant leadership, including teacher self-worth, teacher competence, creating a positive school climate, applying leadership based on local circumstances, and developing vision and mission. vi) managing the distribution of power. Additionally, the study's findings demonstrate that Cronbach Alpha has a dependability of 0.981. Since this instrument can be used during the real study stage because the Cronbach Alpha score is more than 0.7. Pengembangan dan validasi alat untuk mengevaluasi komponen kepemimpinan yang melayani kepala sekolah dasar dalam konteks lokal adalah tujuan dari penelitian ini. Hal ini disebabkan karena sebagian besar instrumen yang digunakan sekarang berasal dari barat dan karena itu kurang cocok untuk digunakan di sekolah-sekolah Malaysia. Tiga spesialis kepemimpinan yang melayani menguji validitas ukuran tersebut. Rancangan kuantitatif penelitian ini kemudian diuji reliabilitasnya dengan menggunakan SPSS 26.0. Selain itu, peneliti menguji indeks reliabilitas instrumen dengan menggunakan Cronbach Alpha. Kemudian, 25 instruktur yang mengajar di wilayah Miri dan dipilih secara acak untuk melengkapi instrumen yang terdiri dari 40 item ini, diberikan salinannya melalui Google Form. Alat ini dibuat untuk menilai enam (6) aspek kepemimpinan yang melayani, antara lain harga diri guru, kompetensi guru, menciptakan iklim sekolah yang positif, menerapkan kepemimpinan berdasarkan keadaan setempat, dan mengembangkan visi dan misi. vi) mengelola distribusi kekuasaan. Selain itu, temuan penelitian ini menunjukkan bahwa Cronbach Alpha memiliki ketergantungan 0,981. Karena instrumen ini dapat digunakan pada tahap pembelajaran sesungguhnya karena skor Cronbach Alpha lebih dari 0,7.